Environmental factors predicting blood lead levels in pregnant women in the UK: the ALSPAC study. - Caroline M Taylor; Jean Golding; Joseph Hibbeln; Alan M Emond (PLoS ONE)
Background Lead is a widespread environmental toxin. The behaviour and academic performance of children can be adversely affected even at low blood lead levels (BLL) of 5-10 µg/dl. An important contribution to the infant's lead load is provided by maternal transfer during pregnancy. Objectives Our aim was to determine BLL in a large cohort of pregnant women in the UK and to identify the factors that contribute to BLL in pregnant women. Methods Pregnant women resident in the Avon area of the UK were enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC) in 1991-1992. Whole blood samples were collected at median gestational age of 11 weeks and analysed by inductively coupled plasma dynamic reaction cell mass spectrometry (n = 4285). Self-completion postal questionnaires were used to collect data during pregnancy on lifestyle, diet and other environmental exposures. Statistical analysis was carried out with SPSS v19. Results The mean±SD BLL was 3.67±1.47 (median 3.41, range 0.41-19.14) µg/dl. Higher educational qualification was found to be one of the strongest independent predictor of BLL in an adjusted backwards stepwise logistic regression to predict maternal BLL <5 or ≥5 µg/dl (odds ratio 1.26, 95% confidence interval 1.12-1.42; p<0.001). Other predictive factors included cigarette smoking, alcohol and coffee drinking, and heating the home with a coal fire, with some evidence for iron and calcium intake having protective effects. Conclusion The mean BLL in this group of pregnant women is higher than has been found in similar populations in developed countries. The finding that high education attainment was independently associated with higher BLL was unexpected and currently unexplained. Reduction in maternal lead levels can best be undertaken by reducing intake of the social drugs cigarettes, alcohol and caffeine, although further investigation of the effect of calcium on lead levels is needed.